Rates and predictors of hospital visits after “Possible AF” alerts from a home ECG monitor in older adults with hypertension: A sub-analysis of the Omron Heart Study - Yusuke Kakei; Keitaro Senoo; Arito Yukawa; Kohei Kawai; Masahiro Makino; Jun Munakata; Nobunari Tomura; Satoshi Shimoo; Hirokazu Shiraishi; Satoaki Matoba (PLoS ONE, 2026)
Background Home ECG can detect atrial fibrillation (AF), but patients’ hospital visit behavior after “possible AF” alerts remains uncertain. We assessed the rates, timing, and correlates of hospital visits following “possible AF” alerts in older adults with hypertension. Methods and findings In a nationwide, decentralized cohort in Japan, 4,078 individuals aged ≥60 years enrolled; 3,820 were analyzed after exclusions. Participants used a home BP monitor equipped with a 30-s single-lead ECG capable of detecting “possible AF”, twice daily for 3 months. Of 1,700 participants who received ≥1 “possible AF” alert, 399 (23.5%) reported an alert-prompted healthcare facility visit within 3 months, and 289 (17.0%) underwent additional testing. Among 175 participants with valid visit dates, the median time to visit was 28 days (mean 36.4). In multivariable models, factors associated with lower odds of a hospital visit included age < 65 years (OR 0.75, 95% CI 0.59–0.95, p = 0.016), current drinking (OR 0.73, 0.57–0.95, p = 0.018), no daily palpitations (OR 0.69, 0.50–0.95, p = 0.022), and no palpitations on the alert day (OR 0.51, 0.30–0.85, p = 0.010). Notably, 105 of 220 (47.7%) participants with physician-adjudicated AF remained without a clinical diagnosis at 12 months. Conclusions In this cohort of older, hypertensive individuals, follow-up rates after a “possible AF” alert were low; fewer than one in four individuals visited a healthcare facility, and fewer than one in five underwent additional testing within 3 months. Hospital visits were less common among younger participants, those who consume alcohol, and those without palpitations. These findings highlight significant gaps between mHealth alerts and subsequent clinical action.